Effect of sulfur on the scintillation properties of mixed ZnSxSe1–x crystals - Trubaieva, O. G.; Chaika, M. A.; Zelenskaya, O. V.; Lalayants, A. I.; GalkinS. М. (Technology and design in electronic equipment, 2018)
ZnSxSe1–x based luminescent materials are promising for use as X-ray and γ-ray detectors. The main advantage of ZnSxSe1–x crystals is the possibility of making of solid solutions over an entire X-range. It was found that varying the composition of ZnSxSe1–x crystals can change their luminescent properties. Many studies were focused on obtaining ZnSxSe1–x mixed crystals, most using a vapour phase growth methods, and only some of works used the directional solidification. The directional solidification techniques allow growing large ZnSxSe1–x crystals for high-energy particles detectors. Practical use, however, requires the knowledge about luminescent properties of ZnSxSe1–x bulk crystals. This study reports the effect of sulfur content on basic properties of ZnSxSe1–xx bulk crystals grown by Bridgman- Stockbarger method. Six different compounds were studied: ZnS0.07Se0.93, ZnS0.15Se0.85, ZnS0.22Se0.78, ZnS0.28Se0.72, ZnS0.32Se0.68, ZnS0.39Se0.61. The ZnSe(Al) and ZnSe(Te) crystals grown at the similar conditions were used as reference. X-ray luminescence was studied using РЕИС-И (REIS-I) X-ray source (Cu, U = 10—45 kV). КСВУ-23 (KSVU-23) spectrophotometer was used to analyse the emission spectra. The afterglow level η (%) was determined by Smiths Heimann AMS-1 spectrophotometer at excitation by such X-ray and γ-ray sources as 123Cs and 241Am (59.5 keV). Light output is one of the main characteristics of the scintillator, which determines its quality as a detector. The ZnSxSe1–x crystals demonstrated increase in the intensity of X-ray induced luminescence spectra with increasing of sulfur content and reached maximum for ZnS0.22Se0.78 composition. Light output of ZnSxSe1–x bulk crystals are higher than those of ZnSe(Te) and ZnSe(Al) commercial crystals. Moreover, thermal stability of scintillation light output of ZnSxSe1–x bulk crystals are also better than those. This investigation has revealed that basic properties of ZnSxSe1–x based scintillation detectors are better than those of ZnSe(Te) and ZnSe(Al).